Lessons from a large‐scale systems dynamics modeling project: the example of the biomass scenario model. (28th March 2019) - Peterson, Steve; Bush, Brian; Inman, Daniel; Newes, Emily; Schwab, Amy; Stright, Dana; Vimmerstedt, Laura
Abstract: The biomass scenario model (BSM) is a dynamic model of the biomass‐to‐biofuels supply chain in the U.S.A., developed during a multi‐year analysis effort conducted by the National Renewable Energy Laboratory (NREL), under sponsorship from the United States Department of Energy (DOE) Bioenergy Technologies Office (BETO). The BSM project, which received the 2018 Applications Award by the International System Dynamics Society, has supported collaborative analyses, developed scenarios for industry development and facilitated stakeholder engagement. We summarize insights gained from the BSM project that may be useful to other large‐scale dynamic modeling efforts. We summarize the project focus, the analysis process, key outcomes and observations on successful execution of such a product. Key points include the value of a multidisciplinary team with clear roles, engagement of experts and stakeholders, and use and reuse of simple, modular structures. The overall effort suggests that these practices may aid long‐term, team‐focused, multi‐stakeholder modeling efforts. © 2019 System Dynamics Society